List of Spanish Seamen in ports in the United Kingdom with particulars of age and qualification
List of Spanish Seamen in Ports in the United Kingdom with Particulars of Age and Qualification. Port. Age. Qualification. BELFAST. Luis DIAZ de Lasaga 54 Captain. Julian de Iribar e Ydoyaga Captain. BRISTOL. Felix R. Pacheco Captain. CARDIFF. Santos BASAURI Equsquiaguirre 51 Captain. Jose ORPI Palan 57 Captain Antonio LARRASQUITO Mugica 22 Deck Officer Juan LARRASQUITU Torre 53 Captain Eduardo del PRADO Rojas 48 First Mate. LIVERPOOL. Benigno BARANANO 45 Chief Engineer. Francisco CORBERA 29 Cook. Pedro ITURREGUI 60 Chief Engineer. Paulin ZARATE 24 Cook. Pedro DOMÍNGUEZ 38 Fisherman NEWCASTLE. Jose GUILLEN Olveira Stoker. SUNDERLAND. Angel and Miss AGUIRRE Captain. WEST HARTLEPOOL. Vicente FERNANDEZ 53 Seaman. Primitivo GONZALEZ 52 Seaman. 292/946/25a/4